Pengembangan Media Pembelajaran Video Menggunakan Sparkol Videoscribe Pada Materi Statistika Kelas IV SD - Azania Khairani; Siti Quratul Ain (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
The purpose of this research is to develop learning media in the form of videos using the sparkol videoscribe application which is appropriate to help the mathematics learning process in statistics material. This research method uses development research with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) but the researchers only use three stages, namely Analysis, Design, and Development. The instruments used in this study were interview guidelines and validation sheets consisting of material expert validation sheets, media expert validation and linguist validation. Data analysis using descriptive statistics in the form of calculating the average score. Based on the results of the study, an assessment of the videoscribe media from the material expert assessment obtained a valid category with a percentage of 91.87%. The media expert's assessment got a valid category with a percentage of 93.35%. The assessment of linguists is in the valid category with a percentage of 93.74%. From these results, the developed videoscribe media is in the valid category so that the videoscribe learning media can be used in the classroom.